Comparative evaluation of Gluma® desensitizer versus Iontophoresis with 1.23% Acidulated phosphate fluoride gel for the treatment of dentinal hypersensitivity after periodontal therapy - Dr. Juilee Umbarkar, Dr. K. Rajashekar,Dr. Neelam Gavali, Dr. Naresh Kumar K, Dr Ravindra Soni, Dr Hiroj Bagde (Drugs and Cell Therapies in Hematology, 2021)
Dentinal hypersensitivity may be defined as pain arising from exposed dentin, typically in response to tactile, thermal, chemical, or osmotic stimuli that cannot be explained as arising from any other form of dental defect or pathology. Root dentin sensitivity is the term used to describe the sensitivity which occurs due to periodontal disease and its treatment. Non-surgical periodontal treatment may temporarily increase root dentin sensitivity which reduces subsequently over period of time. A total of 100 dentinal hypersensitivity patient were selected from the OPD of Department of Periodontology. The results show that root sensitivity was reduced in both the groups over period of 7 days, 1 month and 3 months after treatment of dentinal hypersensitivity Thus, both the treatments modalities are effective in treating root sensitivity following periodontal treatment. In the present study APF gel iontophoresis proved to be more effective for long term use than GD®. It is safe to use iontophoresis unit in the treatment of root sensitivity caused after periodontal treatment. Thus, after analyzing and evaluating the data, it can be concluded that root sensitivity post periodontal treatment which is an enigma to the Periodontists can be effectively treated with Gluma® desensitizer and APF gel iontophoresis, these treatment modalities can be an effective alternative option to other commercially available agents in the market.